Intersex variations, social class, and the postcolonial geopolitics of language and healthcare in Hong Kong - Brian W. King (Discourse & Communication, 2026)
In this study I examine how clinicians’ talk about intersex variations in Hong Kong constructs parents as differently educable biopolitical managers of their children, in ways closely tied to social class and to the colonial language economy of English and Cantonese. Using interactional sociolinguistics and stance‑taking analysis informed by Kiesling’s intersubjective stance framework, interviews are seen as sites where evaluation, alignment, and investment are negotiated in accounts of communication with families in hospitals. English is repeatedly positioned as a professional language, indexing expertise yet also a “trap” of jargon, while Cantonese is framed as affective, pedagogically demanding, and lexically deficient for specialized knowledge. Furthermore, clinicians differentiate “highly educated” parents, imagined as aligned with English‑mediated biomedical discourse and able to “grasp” complex genetic explanations, from “lower socio‑economic class” families portrayed as “fixated” on questions judged as basic. Clinicians also point to a lack of formal training in explaining intersex variations in Cantonese, reliance on ad hoc translations and Google searches, and routine translanguaging in which English technical terms circulate as high‑value epistemic tokens. I argue that such stances reproduce classed hierarchies of linguistic legitimacy and parental rationality, enacting biopolitical inclusion and exclusion in care via linguistic inequity.